2008
DOI: 10.1158/1055-9965.epi-07-2800
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Receipt of Fecal Occult Blood Test versus Endoscopy among Filipino American Immigrants

Abstract: Results: Of the 487 respondents included in this analysis, 257 (53%) had never received any type of colorectal cancer screening. Among the 230 subjects who had ever received a routine screening test, 78 had fecal occult blood test only (16% of the total sample), and 152 had endoscopy with or without fecal occult blood test (31% of the total sample). After controlling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
3
22
3
Order By: Relevance
“…These sites can reach individuals who do not have a regular health care provider, and in fact, 40 % of the participants in our study reported that they did not have health insurance. Our implementation trial succeeded in reaching Filipino Americans who have low levels of income and lack of health insurance-two characteristics that have been shown to be associated with lack of CRC screening among Filipino Americans and other ethnic groups [42][43][44]. Several of these community-based trials have shown good intervention effect sizes and programs in community settings may have promise for reducing disparities in CRC …”
Section: Original Researchmentioning
confidence: 99%
“…These sites can reach individuals who do not have a regular health care provider, and in fact, 40 % of the participants in our study reported that they did not have health insurance. Our implementation trial succeeded in reaching Filipino Americans who have low levels of income and lack of health insurance-two characteristics that have been shown to be associated with lack of CRC screening among Filipino Americans and other ethnic groups [42][43][44]. Several of these community-based trials have shown good intervention effect sizes and programs in community settings may have promise for reducing disparities in CRC …”
Section: Original Researchmentioning
confidence: 99%
“…The third model included all predisposing and enabling factors, and model 4 contained only predictors that were significant in model 3 at " = . 10. Lastly, model 5 tested past screening experience with the significant predictors from models 2 and 4.…”
Section: Cancer Screening Outcomesmentioning
confidence: 99%
“…3,9Y11 Residence in the United States was not related to screening in one study, 3 but percentage of time in the United States was positively related to endoscopic screening in another study. 10 In aggregated Asian study samples, several Asian subgroups had significantly lower rates of screening for all types of cancer compared with non-Hispanic whites, even after adjusting for access to healthcare. 3 Nativity, years in the United States, and English-language fluency were also significantly associated with lower rates of CRC and breast cancer screening.…”
mentioning
confidence: 96%
See 2 more Smart Citations